An outbreak of colibacillosis in a broiler farm - Nur Hardy Bin Abu Daud; Nwe Nwe Htin; Farah Hanif Paan; Than Kyaw; Aung Tun Khaing; Yusuf Abba; Faez Firdaus Jesse Abdullah (2014)
Escherichia coli is one of the most economically important bacteria responsible for early chick mortality in poultry farms worldwide. In this report, researchers investigated a case of sporadic mortality (15%) in 15-18 days old cobb 500 broiler chicks. The chicks were weak with respiratory distress and non-uniform growth rate. Postmortem examination showed evidence of polyserositis with fibrinous hepatitis, pericarditis, peritonitis and air sacculitis as the major findings observed. Bacteriological culture of affected organs showed evidence of E. coli growth on blood agar. The bacteria was found to be resistant to amoxicillin, clindamycin, streptomycin and trimethroprim while intermediate susceptibility to oxytetracyclin and susceptibility to gentamycin were equally observed. The chicks were treated with gentamycin (5-10 mg kg-1 orally) for 5 days and multivitamin (5 g L-1) was given in drinking water for 3 days. Prompt diagnosis and treatment of cases of colibacillosis is crutial to ensuring optimal productivity in poultry farms